1987
DOI: 10.1159/000132342
|View full text |Cite
|
Sign up to set email alerts
|

Integration sites of human papillomavirus 18 DNA sequences on HeLa cell chromosomes

Abstract: Human papillomaviruses (HPV) 16 and 18 are closely linked with human genital cancer. In most cervical carcinomas, viral sequences are integrated into the host genome. HeLa, a cervical carcinoma cell line, has multiple copies of integrated HPV 18 DNA. In this study, in situ chromosome hybridization was used to assign the integration sites of HPV 18 DNA sequences on HeLa cell chromosomes. Four sites of hybridization were identified at 8q23→q24, 9q31→q34, p11→p13 on an abnormal chromosome 5, and q12→q13 on an abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(72 citation statements)
references
References 11 publications
(13 reference statements)
3
65
1
Order By: Relevance
“…This strongly suggests that integration at those particular sites might have conferred some growth advantages to the cells and might have thus been crucial in their immortalization and their selection. In agreement with our results, in situ hybridization analyses on chromosomes have described HPV-16 or -18 integrated at a single site within cervical carcinomas [30] or cervical carcinoma cells such as SW756 [31], SiHa [32] or C4-I [33] cell lines, even though HeLa and Caski cells were shown to harbor HPV-18 and HPV-16 respectively at several distinct sites [32,34,35]. From those localization studies, it appeared that HPV integration sites were frequently mapped in regions containing oncogenes or fragile sites [10,11].…”
Section: Discussionsupporting
confidence: 92%
“…This strongly suggests that integration at those particular sites might have conferred some growth advantages to the cells and might have thus been crucial in their immortalization and their selection. In agreement with our results, in situ hybridization analyses on chromosomes have described HPV-16 or -18 integrated at a single site within cervical carcinomas [30] or cervical carcinoma cells such as SW756 [31], SiHa [32] or C4-I [33] cell lines, even though HeLa and Caski cells were shown to harbor HPV-18 and HPV-16 respectively at several distinct sites [32,34,35]. From those localization studies, it appeared that HPV integration sites were frequently mapped in regions containing oncogenes or fragile sites [10,11].…”
Section: Discussionsupporting
confidence: 92%
“…There was a high correlation between the individual locations of HPV integration sites and fragile sites in the genome since 40 of 57 mapped HPV integration sites were found near fragile sites. These observations con®rm data of other investigators, who have reported HPV integration sites near fragile sites in various cell lines and very few cervical carcinoma samples (Popescu et al, 1987;Smith et al, 1992;Thorland et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Most more detailed studies on the structural analysis of integrated viral genomes in cervical carcinoma cells or their precursors have been performed on a limited number of cervical cancer cell lines including the wellcharacterized HPV18 positive cell lines HeLa, SW756, and C4-1, as well as the HPV16 positive cell lines Caski and SiHa (Couturier et al, 1991;el Awady et al, 1987;Mincheva et al, 1987;Popescu et al, 1987). Due to the limited material available from primary HPV associated cancers and their precursors and the complex technology required to characterize the integration sites in detail, only few integration sites have been suciently investigated in primary lesions.…”
Section: Introductionmentioning
confidence: 99%
“…More recent CGH studies have revealed a high level copy increase of 5p to be a recurrent event during progression of advanced stage CaCx (Heselmeyer et al, 1997;Kirchhoff et al, 1999;Ried et al, 1999;Matthews et al, 2000). Similar markers have been observed in HPV-transformed cell lines (Miller et al, 1971;Durst et al, 1987;Popescu et al, 1987;James et al, 1989;Smith et al, 1989;Macville et al, 1999). Gain of 5p, however, is not observed in low-grade lesions or HR HPV containing keratinocyte cell lines at early passage in vitro (Cottage et al, 2001).…”
Section: Introductionmentioning
confidence: 63%